Familial Kaposi's Sarcoma: A Report of Five Cases from Greece - Kalliopi Armyra; Anargyros Kouris; Arsinoi Xanthinaki; Alexandros Stratigos; Irene Potouridou (Hindawi Limited, 2014)
Introduction. Familial cases of Kaposi's sarcoma have rarely been reported. Kaposi's sarcoma is not uncommon in Greece; its incidence is estimated at 0.20 per 100.000 habitants, showing an increased predominance in the Peloponnese, in Southern Greece. Case Report. We describe five cases of familial clustering of KS originating from Greece. Discussion. The pathogenesis of familial Kaposi's sarcoma is still far from being completely understood. Genetic, environmental, and infectious factors have been incriminated.